2011
DOI: 10.1155/2011/982507
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Abdominal Hypertension and Gastrointestinal Symptoms in Mechanically Ventilated Patients

Abstract: Background. We aimed to describe the incidence of intra-abdominal hypertension (IAH) and gastrointestinal (GI) symptoms and related outcome in mechanically ventilated (MV) patients. Methods. Intra-abdominal pressure (IAP) and gastric residual volumes were measured at least twice daily. IAH was defined as a mean daily value of IAP ≥ 12 mmHg. Results. 398 patients were monitored for all together 2987 days. GI symptom(s) occurred in 80.2% patients. 152 (38.2%) patients developed IAH. Majority (93.4%) of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Combining enteral diet tolerance and IAP values, Reintam et al (23) developed a GI failure score with prognostic value for ICU mortality. In that study the authors did not assess the possible link between IAP and EN tolerance, though in a later trial [27], they reported no such relationship. However, they did note that patients with both high IAP and signs of diet intolerance had worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Combining enteral diet tolerance and IAP values, Reintam et al (23) developed a GI failure score with prognostic value for ICU mortality. In that study the authors did not assess the possible link between IAP and EN tolerance, though in a later trial [27], they reported no such relationship. However, they did note that patients with both high IAP and signs of diet intolerance had worse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, gastrointestinal dysfunction can lead to IAH and vice versa. IAP is not a direct indicator of gastrointestinal function, which may confuse the relationship between gastrointestinal symptoms and IAP [37]. In that sense, intestinal ultrasonography has certain advantages over other methods used previously by practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of intraabdominal hypertension (IAH) and measurement of IAP is described elsewhere [27]. In a study in mechanically ventilated patients, the presence of IAH in the absence of GI symptoms was not associated with mortality [28].…”
Section: Other Monitoring Optionsmentioning
confidence: 99%